The teaching of medical ethics to medical students. - Glick, S M (1994)
Teaching medical ethics to medical students in a pluralistic society is a challenging task. Teachers of ethics have obligations not just to teach the subject matter but to help create an academic environment in which well motivated students have reinforcement of their inherent good qualities. Emphasis should be placed on the ethical aspects of daily medical practice and not just on the dramatic dilemmas raised by modern technology. Interdisciplinary teaching should be encouraged and teaching should span the entire duration of medical studies. Attention should be paid particularly to ethical problems faced by the students themselves, preferably at the time when the problems are most on the students' minds. A high level of academic demands, including critical examination of students' progress is recommended. Finally, personal humility on the part of teachers can help set a good example for students to follow.